2009
DOI: 10.1111/j.1365-2672.2009.04244.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional, genetic and chemical characterization of biosurfactants produced by plant growth-promotingPseudomonas putida267

Abstract: Aims:  Plant growth‐promoting Pseudomonas putida strain 267, originally isolated from the rhizosphere of black pepper, produces biosurfactants that cause lysis of zoospores of the oomycete pathogen Phytophthora capsici. The biosurfactants were characterized, the biosynthesis gene(s) partially identified, and their role in control of Phytophthora damping‐off of cucumber evaluated. Methods and Results:  The biosurfactants were shown to lyse zoospores of Phy. capsici and inhibit growth of the fungal pathogens Bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
80
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(86 citation statements)
references
References 37 publications
3
80
0
3
Order By: Relevance
“…Despite the many potential roles of biosurfactants on leaves, only a few studies have examined their production in the phyllosphere (10,(12)(13)(14)(15)(16)(17). Furthermore, these studies have focused only …”
mentioning
confidence: 99%
“…Despite the many potential roles of biosurfactants on leaves, only a few studies have examined their production in the phyllosphere (10,(12)(13)(14)(15)(16)(17). Furthermore, these studies have focused only …”
mentioning
confidence: 99%
“…Published reports show plant and clinical strains of Pseudomonas (e.g., Pseudomonas putida, P. fluorescens, and other Pseudomonas spp.) produce secondary antimicrobial metabolites, including enzymes, volatiles (hydrogen cyanide), cyclic lipopeptides, and antibiotics (33)(34)(35). These have been applied in plant pathology to control fungal pathogens and in clinical studies to inhibit pathogenic strains (36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…Infante-Duarte et al [35] demonstrated that the lipopeptides derived from B. burgdorferi stimulate the IL-17 expression (Cytokine produced by activated murine cytotoxic T-cells) in both murine and human T H cells. They induce the IL-17 expression together with TNF-α, so are coexpressed with other proinflammatory cytokines.…”
Section: Lipopeptides As Immunomodulatorsmentioning
confidence: 99%